Necesidad de regular la tasa del impuesto a la plusvalía y utilidades provenientes de la transferencia de inmuebles urbanos, establecida en el Código Orgánico de Organización Territorial, Autonomía y Descentralización - Rojas Sinche, Pablo Ramiro (2015)
The Constitution of the Republic of Ecuador, clearly determined that the autonomous governments enjoy political, administrative and financial autonomy, so that within their powers, the GAD have the power to issue regulations through ordinances that apply within their territorial boundaries. This is why considering important to determine how it affects the rate of tax on capital gains and profits, the citizen, that I found it necessary to investigate and suggest the "NEED FOR REGULAR RATE OF CAPITAL GAINS TAX AND PROFIT FROM THE URBAN PROPERTY TRANSFER ESTABLISHED IN THE ORGANIC CODE OF TERRITORIAL ORGANIZATION, autonomy and decentralization ", was raised as a general objective to analyze legal and doctrinally the Civil Code, with respect to adverse possession; taking it for testing, applying methods and techniques of scientific, obtaining significant results on which to base the proposal. In order to meet the goals outlined in the research project, a literature research that underpinned the whole process, which could know better the topic of taxes and their treatment in the different existing legal bodies was performed, well supported by valid criteria of different writers familiar with the problems. In conducting field research, applying a survey of 30 professionals from the field of law, valuable data that helped establish that the rate of tax on capital gains and profits, excessive obtained; well that does not match the reality that currently exists in the country, seriously affecting the economy of citizens. It was fully demonstrated the need for a reform COOTAD to better regulate the aforementioned tax